PLURALISME ASIMETRIS: PLURALITAS DAN GERAKAN SOSIAL MASYARAKAT INDONESIA KONTEMPORER - Muhammad Abzar Duraesa; Muzayyin Ahyar (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This study aims to look at the diversity condition of Indonesian society related to the discourse of pluralism. Based on the fieldwork conducted from several regions in Indonesia; Samarinda, Manado, and Jakarta which is considered as representative regions in term of its dynamic diversity, by using a socio-political approach, the results of this study show that the condition of diversity in Indonesian society constitutes an asymmetrical discourse of pluralism; a plurality based on social conditions and phenomena that differ from one region to another, one community to another, and one case to another. The concept of pluralism does not merely a notion that emerge because of religious diversity and does not always shape people's behavior in facing diversity. On the contrary, the diversity of Indonesian society will enrich the concept of pluralism to be an ethnic, religious, and political pluralism.